2015
DOI: 10.1165/rcmb.2013-0021oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNA-150 and Glycoprotein Nonmetastatic Melanoma Protein B in Angiogenesis during Hyperoxia-Induced Neonatal Lung Injury

Abstract: Glycoprotein nonmetastatic melanoma protein B (GPNMB), a transmembrane protein, has been reported to have an important role in tissue repair and angiogenesis. Recently, we have demonstrated that hyperoxia exposure down-regulates microRNA (miR)-150 expression and concurrent induction of its target gene, GPNMB, in neonatal rat lungs. This study aimed to test the hypothesis that soluble GPNMB (sGPNMB) promotes angiogenesis in the hyperoxic neonatal lungs. Wild-type (WT) or miR-150 knockout (KO) neonates, exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…In addition, lack of miR-150 significantly exacerbated CNV lesions in the laser-induced CNV model and increased sprouting in aortic ring and choroidal explants, further supporting an antiangiogenic effect of miR-150. These findings are consistent with another study showing increased lung angiogenesis in miR-150 −/− mice in a model of oxygen-induced neonatal lung injury (29). Although these data strongly support a primarily direct effect of vascular-enriched miR-150 on endothelial function and ocular angiogenesis, we cannot rule out potential contributions from circulating miR-150, which was found in monocytederived microvesicles to regulate target genes in the recipient ECs and affect pathological angiogenesis in tumor and diabetic models (30,31).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, lack of miR-150 significantly exacerbated CNV lesions in the laser-induced CNV model and increased sprouting in aortic ring and choroidal explants, further supporting an antiangiogenic effect of miR-150. These findings are consistent with another study showing increased lung angiogenesis in miR-150 −/− mice in a model of oxygen-induced neonatal lung injury (29). Although these data strongly support a primarily direct effect of vascular-enriched miR-150 on endothelial function and ocular angiogenesis, we cannot rule out potential contributions from circulating miR-150, which was found in monocytederived microvesicles to regulate target genes in the recipient ECs and affect pathological angiogenesis in tumor and diabetic models (30,31).…”
Section: Discussionsupporting
confidence: 93%
“…Bhaskaran et al ( 24 ) confirmed that one of the miR-150 targets was glycoprotein nonmetastatic melanoma protein b (GPNMB), which may participate in the regulation of angiogenesis. Narasaraju et al ( 26 ) further confirmed the regulatory role of miR-150 in angiogenesis in BPD. Dong et al ( 25 ) found that miR-29 expression was upregulated in BPD and suggested that miR-29 may suppress lung development by inhibiting Ntrk2.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have also shown that epigenetic regulation by microRNA expression is aberrant in BPD [76, 77]. Transgenic miR-150 knockout mice demonstrate increased angiogenesis when exposed to neonatal hyperoxia that may be due to upregulation of glycoprotein non-metastatic melanoma protein B (GPNMB) [78]. Differential regulation of gene expression by these and other mechanisms may explain previous observations that mechanical ventilation and oxygen therapy increase antiangiogenic gene expression (thrombospondin-1, endoglin) and decrease expression of angiogenic genes (VEGFB, VEGFR2, Tie-2) [79, 80].…”
Section: Introductionmentioning
confidence: 99%